Doing business in Bolivia: A case study in the Andean regulatory framework - Jorge Ignacio Del Castillo Machicado (Institute for Advanced Development Studies (INESAD), 2020)
This article researches on the evolution of the business regulatory framework of Bolivia from 2006 to 2017 and its relationship with the country's Labor productivity, Total Factor Productivity, and its Informal Economy size. To do this, it analyzes the Doing Business annual reports and standardizes each year overall score to the most recent methodology developed by the World Bank Group. Furthermore, it complements its finding with qualitative data through semi-structured interviews to key actors in the Bolivian economy. Overall, this paper finds that few steps have been taken to improve Bolivia's Business regulatory framework from the period of 2006-2017, result in a lower rank in the Doing Business report and keeping its score constant. The lack of initiative in working towards more efficient policies, complex nature and poor adaptability of new technological practices have stagnated the improvements of business regulations along their lifecycles. As a consequence, Bolivia Total Factor Productivity, Informal Economy size and Labor productivity have shown no improvement over the last 10 years.
Keywords: D23; H11; H21; 330; World Bank; doing business; business regulatory framework; productivity; informality; Bolivia